On Efficient Estimation of the Population Mean under Stratified Ranked Set Sampling. (6th October 2022) - Bhushan, Shashi; Kumar, Anoop; Shahab, Sana; Lone, Showkat Ahmad; Akhtar, Md Tanwir
Abstract : This paper considers some efficient combined and separate classes of estimators of the population mean in the presence of bivariate auxiliary information under stratified ranked set sampling. The mean square error MSE expressions of the proffered combined and separate classes of estimators are derived to the first order of approximation. The theoretical conditions are obtained under which the proffered combined and separate classes of estimators perform better than the existing combined and separate class of estimators. Subsequently, numerical and simulation studies are performed using real and artificially generated populations. The numerical and simulation results are found to be rewarding, showing the superiority of the proffered estimators over the existing estimators.